Blair Davis. Movie Comics: Page to Screen/Screen to Page. New Brunswick: Rutgers UP, 2016. - Violeta Martínez-Alcañiz (Studies in 20th & 21st Century Literature, 2017)
Review of Blair Davis. Movie Comics: Page to Screen/Screen to Page. New Brunswick: Rutgers UP, 2016.
Keywords: movie comics; Davis